The interaction of derma collagen with mineral and polymer compounds - Отрошко, Валентина Анатоліївна; Мережко, Ніна Василівна; Мокроусова, Олена Романівна (Technology audit and production reserves, 2016)
Analysis of the existing research aimed at expanding the range of filling and retanning materials and increasing environmental leather industry showed that the actual trend is the use of compositions based on bentonite clay. To assess the effectiveness of the developed polymer-mineral compositions is expedient to establish the nature of the interaction between the surface of the material and collagen to predict the effectiveness of structuring the derma and rational use of chemical compounds created in the leather production. IR spectroscopy was chosen for the experiment. The object of this article is the infrared spectroscopic study of the interaction of the derma collagen with modified montmorillonite and acrylic emulsion. As a result of analysis of the infrared spectra it was concluded that mineral and polymer compounds can significantly change the structure of semi-finished chrome through the formation of bonds of various nature: coordination, electrovalent, hydrogen bonds and van der Waals forces. The most likely is the formation of new types of hydrogen bonds Si-O....H-N and Si-O....H-C between the active centers of modified montmorillonite and NH- and CH- protein groups. Interact with chrome gelatin in the case of use of acrylic polymers is involving carboxyl and carbonyl groups of MBM-3 and amino, ester, peptide groups ionized groups СOO- and NH3 + of chrome gelatin. Such interaction will promote the efficient structuring of the collagen structure of the derma in the following manufacturing processes and improve operational properties of the leather.